Current understanding of probiotics and sinonasal inflammation: A review - Saud Romaih Alromaih; Nouf Mohammad Aloraini (Wolters Kluwer Medknow Publications, 2020)
The complex interplay between commensal sinonasal microbiota and pathogenic bacteria contributes to the development of sinonasal inflammatory diseases. This review describes the rationale, effectiveness, and safety of probiotics in sinonasal inflammatory diseases. In vitro and animal clinical trials demonstrated a promising effect of probiotics in decreasing inflammation and the proportion of pathologic bacteria and improving the outcome. However, human studies involving chronic rhinosinusitis (CRS) patients did not exert any significant effect in reducing the symptoms, except in one study reported improvements in CRS exacerbations. This review concluded that up to now, the value of probiotics usage is not well understood, and future research aiming to extend the understanding of it will contribute to enhance the effectiveness of probiotic use in sinonasal inflammatory diseases.